Mott versus Slater-type metal-insulator transition in Mn-substituted SrSr 3Ru 2O 7 - Hossain, Suman; Haverkort, Maurits W.; Hu, Zhimin (Physical review. B, Condensed matter and materials physics, 2012)
We present a temperature-dependent x-ray-absorption (XAS) and resonant elastic x-ray scattering (REXS) study of the metal-insulator transition (MIT) in Sr3(Ru1−xMnx)2O7. The XAS results reveal that the MIT drives the onset of local antiferromagnetic correlations around the Mn impurities, a precursor of the long-range antiferromagnetism detected by REXS at Torder<TMIT. This establishes that the MIT is of the Mott type (electronic correlations) as opposed to Slater type (magnetic order). While this behavior is induced by Mn impurities, the (14,14,0) order exists for a wide range of Mn concentrations, and points to an inherent instability of Sr3Ru2O7.